Building a Global Rangelands Data Platform: Safeguarding Rangelands through Data Decision-Making - Domenech, C; Flintan, Fiona E (International Livestock Research Institute, 2025)
Presentation on the Global Rangelands Data Platform being developed as the go-to platform for big data on rangelands. Presentation made at a side event at UNCCD COP 16, December 2025.